Parenting of Islamic Boarding School Santri in the Development of Santri Morals - Heryanto, Deden; Apin, Apin (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2022)
In Indonesia there are many Islamic Religious Institutions, this is because in Indonesia the majority of the population is Muslim. Al-Qur'an Al-Falah Islamic Boarding School is one of the Islamic boarding schools located in West Java which has been established since 1970. This Islamic boarding school is quite old and has a fairly high population in West Java. This study aims to determine the strategies used by pesantren administrators in improving the moral quality of students so that they can become qualities for other students in improving morals and to find out what are the supporting and inhibiting factors of pesantren administrators in instilling moral values. to students. The research method used in this study uses qualitative methods, namely methods to explore and understand individuals or groups of people. The results of this study are strategies that are carried out and applied by pesantren administrators in improving the quality of students, namely by using strategies of providing understanding, discipline, exemplary, advice, supervision and punishment as well as maximizing activities that have moral potential. from students. The supporting factor is the existence of humanism between the administrators and students and the activeness of the pesantren administrators. And the inhibiting factor generally comes from the emotional condition of the students themselves. Keywords: Morals, Strategy, Islamic Boarding School Management, Santri   Abstrak Di Indonesia terdapat banyak sekali pondok pesantren, hal ini karena di Indonesia mayoritas penduduknya beragama Islam. Pondok pesantren Al-Qur’an Al-Falah merupakan salah satu pondok pesantren yang terletak di Jawa Barat yang telah berdiri sejak tahun 1970 pesantren ini terhitung cukup tua dan memiliki populatitas yang cukup tinggi di Jawa Barat. Penelitian ini bertujuan untuk mengetahui strategi yang digunakan oleh pengurus pesantren dalam meningkatkan kualitas akhlak santri sehingga bisa menjadi acuan bagi pondok pesantren lainnya dalam meningkatkan kualitas akhlak santri dan untuk mengatahui apa saja yang menjadi faktor pendukung serta penghambat pengurus pesantren dalam menanamkan nilai-nilai akhlak terhadap santri. Metode penelitian yang digunakan dalam penelitian ini menggunakan metode kualitatif metode ini merupakan metode-metode untuk mengeksplorasi dan memahami individu atau sekelompok orang. Hasil dari penelitian ini adalah strategi yang dilakukan dan diterapkan oleh pengurus pesantren dalam meningkatkan kualitas akhlak santri yaitu dengan menggunakan strategi pemberian pemahaman, kedisiplinan, keteladanan, nasihat, pengawasan dan hukuman serta memaksimalkan kegiatan-kegiatan yang memiliki potensi meningkatnya akhlak santri. Adapun faktor pendukung adanya humanis antara pengurus dengan santri serta keaktifan pengurus pesantren. Dan yang menjadi faktor penghambat secara umum datang dari kondisi emosi santri itu sendiri.     Keywords: Aklak, Strategi, Pengurus Pesantren, Santri